Effects of Destination Image, Tourist Motivation, Service Quality and Perceived Value on Tourist Satisfaction and Loyalty - Heri Setiawan (Faculty of Economics, Universitas Sriwijaya, 2018)
This study aims to examine the causality relationship among destination image, tourist motivation, service quality and perceived value on tourist satisfaction and loyalty. Population in this study was tourists who had visited in four tourist destinations in Palembang namely: Jakabaring Sport City, Kemaro Island, Benteng Kuto Besak and Kambang Iwak Park. The analysis method used in this study is path analysis, with sample of the research were 180 respondents and type of sampling used was purposive sampling. The results indicated that there were significant effects destination image, service quality, perceived value on tourist satisfaction. There was no significant effect tourist motivation on tourist satisfaction. Then, there was a significant effect destination image and tourist satisfaction on tourist loyalty. There was no significant effect perceived value on tourist loyalty.